Differential Pathogenic Th17 Profile in Mesenteric Lymph Nodes of Crohn's Disease and Ulcerative Colitis Patients - Bsat, Marwa; Chapuy, Laurence; Rubio, Manuel; Wassef, Ramses; Richard, Carole; Schwenter, Frank; Loungnarath, Rasmy; Soucy, Geneviève; Mehta, Heena; Sarfati, Marika (Frontiers in Immunology, 2019)
The drug targets IL23 and IL12 regulate pathogenicity and plasticity of intestinal Th17 cells in Crohn’s disease (CD) and ulcerative colitis (UC), the two most common inflammatory bowel diseases (IBD). However, studies examining Th17 dysregulation in mesenteric lymph nodes (mLNs) of these patients are rare. We showed that in mLNs, CD could be distinguished from UC by increased frequencies of CCR6+CXCR3-ROR+Tbet-CD4+ (Th17) memory T cells enriched in CD62Llow effector memory T cells (TEM), and their differentially expressed molecular profile. Th17 TEM cells (expressing IL17A, IL17F, RORC and STAT3) displayed a higher pathogenic/cytotoxic (IL23R, IL18RAP, and GZMB, CD160, PRF1) gene signature in CD relative to UC, while non-pathogenic/regulatory genes (IL9, FOXP3, CTLA4) were more elevated in UC. In both CD and UC, IL12 but not IL23, augmented IFN expression in Th17 TEM and switched their molecular profile towards an ex-Th17 (Th1*)-biased transcriptomic signature (increased IFNG, and decreased TCF7, IL17A), suggesting that Th17 plasticity occurs in mLNs before their recruitment to inflamed colon. We propose that differences observed between Th17 cell frequencies and their molecular profile in CD and UC might have implications in understanding disease pathogenesis, and thus, therapeutic management of patients with IBD.